Prostitution and exploitation child sexual in Uruguay. Opinion of sex workers - Pablo Guerra (Revista Sobre la Infancia y la Adolescencia)
In this article we will present the information obtained in the project entitled "Investigation on conditions of work and opinion on trafficking in persons between population that he exercises the feminine prostitution in Uruguay " from 188 interviews to sexual workers. First we analyse the concept of child prostitution in the frame of the sexual exploitation of children and teenagers, to advance then in the result of the fieldwork. 29 % of the sample expresses to know cases of child prostitution in his areas of work, which confirms a worrying presence of this phenomenon, especially in the street prostitution.  As for the opinion, 77% of the interviewed ones have a negative opinion of the phenomenon.